Epidemiological Monitoring and Antibiotic Therapies of Macrolide-Resistant Mycoplasma pneumoniae in Chinese Patients With Community-Acquired Pneumonia: A Prospective Multicenter Surveillance Study. (4th October 2017) - Yin, Yudong; Wang, Rui; Zhuo, Chao; Wang, Hui; Wang, Minggui; Xie, Canmao; She, Danyang; Yuan, Xin; Wang, Rentao; Cao, Bin; Liu, Youning
Abstract: Background: High prevalence of macrolide-resistant Mycoplasma pneumoniae ( MP) among community acquired pneumonia (CAP) necessitates epidemiological monitoring of resistant patterns of MP isolates against various other antibiotics. Due to rise in resistance by MP strains, optimization of antibiotic therapies is essential in the management of CAP. Methods: We conducted this prospective, multicenter, surveillance study on CAP patients who visited 6 teaching hospitals in China from September 2010 to June 2012. Prevalence of MP among CAP patients was tested by throat swab samples culture and polymerase chain reaction (PCR). To determine the antibiotic resistance and susceptibility, minimum inhibitory concentration (MIC) values were obtained from the antibiotic sensitivity test. Point mutations at 23s rRNA and nucleotide sequences were detected using a Dynamic ET Terminator Cycle Sequencing kit and ABI PRISM 377 DNA sequencer, respectively. The results were compared with macrolide-resistant strains. Results: A total of 520 adult patients (mean age: 45.7 ± 26.2 years) with CAP were enrolled in the study. The prevalence rate of MP positive CAP patients was as low as 14.42% (75/520) in both culture and real-time PCR detection. Macrolide resistance was as high as 80% and 72% against erythromycin (ERY) and azithromycin (AZM) respectively, which were associated with the A2063G transition mutation in domain-V of the 23S rRNA gene. Six strains with mild to moderate ERY-resistance level were still susceptible to AZM, of which only 2 (with MIC value 16 μg/mL and 32 μg/mL) harbored an A2063G transition. Though, tetracycline, minocycline and quinolones (moxifloxacin and fluoroquinolones) had no signs of resistance, the MIC values were on the edge of resistance to quinolones (MIC value of 1.0 μg/mL and 0.5 μg/mL for levofloxacin and moxifloxacin, respectively). Conclusion: MP strains showed high resistance to macrolides but none to fluoroquinolones and tetracyclines. Hence, fluoroquinolones may prove beneficial for treating macrolide resistant MP infections. Nevertheless, the increased MIC values of certain strains for levofloxacin and moxifloxacin, if not optimized, may pave way for quinolone-resistant MP strains in future. Disclosures: All authors: No reported disclosures.